Non-invasive estimation of QLV from the standard 12-lead ECG in patients with left bundle branch block - Melgaard, Jacob; van Dam, Peter M.; Sommer, Anders; Fruelund, Patricia; Nielsen, Jens Cosedis; Riahi, Sam; Graff, Claus (Frontiers in Physiology, 2022)
Background: Cardiac resynchronization therapy (CRT) is a treatment for patients with heart failure and left bundle branch block (LBBB) ECG pattern. CRT resynchronizes ventricular contraction with a right ventricle (RV) and a left ventricle (LV) pacemaker lead. Positioning the LV lead in the latest electrically activated region (measured from Q onset in the ECG to LV sensing by the left pacemaker electrode [QLV]) is associated with favorable outcome. However, optimal LV lead placement is limited by coronary venous anatomy and the inability to measure QLV non-invasively before implantation. We propose a novel non-invasive method for estimating QLV in sinus-rhythm from the standard 12-lead ECG. Methods: We obtained 12-lead ECG, LV electrograms and LV lead position in a standard LV 17-segment model from procedural recordings from 135 standard CRT recipients. QLV duration was measured post-operatively. Using a generic heart geometry and corresponding forward model for ECG computation, the electrical activation pattern of the heart was fitted to best match the 12-lead ECG. This procedure initialized 6 activation sites associated with the His-Purkinje system. The initial timing of each site was based on the directions of the vectorcardiogram (VCG). Timing and position of the sites were then changed iteratively to improve the match between simulated and measured ECG. Noninvasive estimation of QLV was done by calculating the time difference between Q-onset on the computed ECG and the activation time corresponding to centroidal epicardial activation time of the segment where the LV electrode is positioned. The estimated QLV was compared to the measured QLV. Further, the distance between the actual LV position and the estimated LV position was computed from the generic ventricular model. Results: On average there was no difference between QLV measured from procedural recordings and non-invasive estimation of QLV (ΔQLV=-3.0±22.5ms,p=0.12). Median distance between actual LV pacing site and the estimated pacing site was 18.6 mm (IQR 17.3 mm). Conclusions: Using the standard 12-lead ECG and a generic heart model it is possible to accurately estimate QLV. This method may potentially be used to support patient selection, optimize implant procedures, and to simulate optional stimulation parameters prior to pacemaker implantation.